Long‐term effects of very low‐carbohydrate and high‐carbohydrate weight‐loss diets on psychological health in obese adults with type 2 diabetes: randomized controlled trial. (23rd March 2016) - Brinkworth, G. D.; Luscombe‐Marsh, N. D.; Thompson, C. H.; Noakes, M.; Buckley, J. D.; Wittert, G.; Wilson, C. J.
Abstract: Background/Objective: Very low‐carbohydrate, high‐fat (LC) diets are used for type 2 diabetes (T2DM) management, but their effects on psychological health remain largely unknown. This study examined the long‐term effects of an LC diet on psychological health. Methods: One hundred and fifteen obese adults [age: 58.5 ± 7.1 years; body mass index: 34.6 ± 4.3 kg m −2 ; HbA1c : 7.3 ± 1.1%] with T2DM were randomized to consume either an energy‐restricted ( 6 to 7 MJ), planned isocaloric LC or high‐carbohydrate, low‐fat (HC) diet, combined with a supervised exercise programme (3 days week −1 ) for 1 year. Body weight, psychological mood state and well‐being [Profile of Mood States (POMS), Beck Depression Inventory (BDI) and Spielberger State Anxiety Inventory (SAI)] and diabetes‐specific emotional distress [Problem Areas in Diabetes (PAID) Questionnaire] and quality of life [QoL Diabetes‐39 (D‐39)] were assessed. Results: Overall weight loss was 9.5 ± 0.5 kg (mean ± SE), with no difference between groups ( P = 0.91 time × diet). Significant improvements occurred in BDI, POMS (total mood disturbance and the six subscales of anger‐hostility, confusion‐bewilderment, depression‐dejection, fatigue‐inertia, vigour‐activity and tension‐anxiety), PAID (total score) and the D‐39 dimensions of diabetes control, anxiety and worry, sexual functioning and energy and mobility, P < 0.05 time. SAI and the D‐39 dimension of social burden remained unchanged ( P ≥ 0.08 time). Diet composition had no effect on the responses for the outcomes assessed ( P ≥ 0.22 time × diet). Conclusion: In obese adults with T2DM, both diets achieved substantial weight loss and comparable improvements in QoL, mood state and affect. These results suggest that either an LC or HC diet within a lifestyle modification programme that includes exercise training improves psychological well‐being.